Changing subjects digressions in modern American poetry - Reddy, Srikanth, 1973- (New York ; Oxford : Oxford University Press, 2012)
'Changing Subjects' contends that major American poets-such as Walt Whitman, Wallace Stevens, John Ashbery, and Lyn Hejinian-transformed verse and even changed conceptions of modern subjectivity by exploiting an ordinary rhetorical device ubiquitous in spoken language: the digression.
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Includes bibliographical references and index.
Keywords: American poetry -- 20th century -- History and criticism; Moore, Marianne, -- 1887-1972 -- Criticism and interpretation; Hejinian, Lyn -- Criticism and interpretation; Ashbery, John, -- 1927- -- Criticism and interpretation; Whitman, Walt, -- 1819-1892 -- Influence; Digression (Rhetoric) in literature; Poetics